P260 Modulating motor learning using cathodal tDCS. Issue 3 (March 2017) - Hinson, E.; Thein, S.; Stagg, C.
Abstract : Following a stroke, anatomically distinct regions of the motor network including both ipsi- and contralesional areas have been demonstrated to increase when moving the stroke-affected arm. However, it is not clear what this increase in activity represents. Increased activity has been shown to be related to residual hand function in chronic stroke patients, however those patients with the highest levels of activity in these regions also show the worst recovery. Transcranial direct current stimulation (tDCS) is being increasingly investigated for its potential as an adjunct therapeutic tool for rehabilitation due to its ability to modulate underlying cortical excitability and induce the neurochemical changes thought to contribute to plasticity. For optimisation of this tool, a complete understanding of the wider motor network and the regions that could provide compensatory activity is needed. Studies in chronic stroke patients are inherently limited due to the inhomogeneity of lesion volume and location. An alternative is investigated here: the modelling of a stroke-type lesion in healthy participants using cathodal tDCS to temporarily down-regulate activity in a target area of the cortex. Combining cathodal tDCS with a model of motor recovery (a simple motor learning task) during BOLD functional MRI, we hoped to identify candidate regions that might demonstrate compensatory activity. Cathodal tDCS applied to left motor cortex (M1) during an explicit sequence-learning task performed with the right hand, resulted in down-regulation of activity within left M1, with a concurrent, possibly compensatory, increase in activity in the right M1. By contrast, delivery of tDCS prior to the task led to greater learning-related activity changes in left M1, Supplementary Motor Area (SMA) and dorsal premotor cortex (PMd) compared to concurrent and sham stimulation. These results, combined with no significant difference in behavioural performance across the stimulation groups identify that cathodal tDCS induced "virtual lesions" could be a suitable model for stroke lesions and that both ipsi- and contralateral regions could be considered as therapeutic targets for compensatory up-regulation using tDCS in stroke recovery.